Role of Serum Ferritin as An Early Prognostic Marker in Dengue Fever: A Prospective Observational Study (Central Medical College Journal, 2026)
Background: Early detection of progression to severe dengue using simple and measurable tests is crucial for initiating appropriate supportive therapy. This research investigated if blood ferritin levels can be used as a marker of seriousness in individuals with dengue. Methods: A hospital-based, forward-looking study was performed on 70 individuals admitted to the Bangladesh Shishu Hospital & Institute. Dengue diagnoses were made based on NS1 antigen detection on days 2–3 and/or IgM presence on days 6–10. Blood ferritin levels were quantified using ELISA on the day of defervescence. Results: Mean age was 5.5 ± 4.02 years, with 42.9% between 1–5 years and a male predominance (62.9%). Dengue shock syndrome developed in 28.6% of patients. The mean serum ferritin level was 931.50 ± 1009.56 ng/ml. significantly higher levels (2222.60 ± 739.60 ng/ml) were observed in dengue shock syndrome cases. Conclusion: Elevated serum ferritin levels during the defervescence period are significantly associated with dengue shock syndrome and may be used as an early prognostic marker.Central Medical College Journal Vol 9 No 2 July 2025 Page: 64-69